(untitled) (Linguostylistic Studies, 2016)
The article defines the basic principles of compiling explanatory-translation dictionaries, which cover modern Ukrainian normative archaeological terms and their equivalents in the Russian and English languages. The author formulates the main tasks and aims of such a dictionary, the selection criteria of terminological units and the types of semantic and grammatical characteristics of the terms. The paper describes the structure of the dictionary entry, and provides information about the system of lexicographical remarks. The dictionary is compiled in accordance with alphabetical-cluster method, based on the principles of informative importance, normativity and frequency of use of the archaeological terms in the specialized literature. An entry in the dictionary consists of the title word or phrase, which is the object of description, comments regarding the inflection terms, etymological reference to the words of foreign origin, definition and the translation of them. Lexicographic remarks concern the semantic, grammatical, functional and stylistic peculiarities of terms. Key words: archaeological terms, Ukrainian terminography, structure dictionary, article in the dictionary, lexicographic remarks. References